Metaphors in the Lyrics of “Chandelier” by Sia - Salman Hasyim A; Otong Setiawan Djuharie (Jurnal Ilmu Sosial dan Humaniora, 2025)
The findings reveal four distinct types of metaphors employed in the song's lyrics: dead metaphors, creative metaphors, dormant metaphors, and implicit metaphors. For instance, the phrase "holding on for dear life" represents a dead metaphor that effectively conveys the narrator’s desperation. The phrase "swing from the chandelier" exemplifies a creative metaphor, vividly illustrating a reckless escape and celebration of freedom from reality. The dormant metaphor "party girls don't get hurt" highlights the ironic contrast between outward appearances and inner suffering. Lastly, "sun is up, I'm a mess" serves as an implicit metaphor, signaling the shift from temporary escape to harsh reality. Collectively, these metaphors enhance the aesthetic appeal and emotional resonance of the song, ultimately reinforcing its core message about addiction, escapism, and vulnerability. This study contributes to the linguistic understanding of metaphor's role in artistic communication through song lyrics and offers value to scholars, educators, and music enthusiasts alike.